"Dreamland": Black Girls Saying and Creating Space through Fantasy Worlds. Issue 1 (1st March 2022) - Toliver, S.R.
Abstract: The rampant murder of Black women and girls in the United States proves that this place is not safe for them. In fact, it is questionable whether any space currently known can be safe when antiblackness and misogynoir are interwoven into the fabric of our world. For this reason, researchers must explore the unbound landscapes Black girls create for themselves in fantastic narratives. In this article, I examine the fantasy short stories of two Black middle school girls who participated in a writing workshop to explore how they resisted spatial control by creating new worlds they had the power to construct and dismantle.